Is intra‐procedure three‐dimensional transesophageal echocardiogram an alternative to preprocedure multidetector computed tomography for the measurement of the aortic annulus in patients undergoing transcatheter aortic valve replacement?. Issue 8 (18th July 2017) - Hafiz, Abdul Moiz; Medranda, Giorgio A.; Kakouros, Nikolaos; Patel, Jay; Kahan, Jonathan; Gubernikoff, George; Ray, Beevash; Paruchuri, Vijayapraveena; DeLeon, Joshua; Marzo, Kevin; Calixte, Rose; Gaztanaga, Juan
Abstract : Background: The role of three‐dimensional transesophageal echocardiography (3DTEE) vs multidetector computed tomography (MDCT) in aortic annular sizing has been poorly defined in patients undergoing transcatheter aortic valve replacements (TAVR). We set to determine the correlation between 3DTEE and MDCT in measuring the aortic annulus prior to TAVR. Methods: In an observational, retrospective study, we compared aortic annular areas measured by MDCT and 3DTEE in TAVR patients. The aortic annular area was measured by planimetry of images obtained by MDCT pre‐TAVR and by intra‐TAVR TEE using 3D rendering of the aortic annulus followed by planimetry. Our primary outcome was degree of correlation between mean aortic annulus area by 3DTEE and MDCT. Results: Of the 111 consecutive patients undergoing TAVR who had measurements from both modalities available for comparison between February 2012 and April 2015, 87 met inclusion criteria. The mean aortic annular area by MDCT was 4.44±0.88 cm 2 and by 3DTEE was 4.33±0.78 cm 2 . There was a strong positive linear correlation between aortic annular area measurements obtained from these two modalities with mild relative underestimation by 3DTEE (ρ=.833). This relationship can be estimated using the predictive formula: MDCT Aortic Annular Area = 0.605 + 0.878 × 3 DTEE Aortic Annular Area Conclusions: Three‐dimensional transesophageal echocardiography measurements have a high degree of correlation with MDCT measurements and thus can assist in proper valve prosthesis selection for TAVR. Our study thus supports use of 3DTEE as a reasonable alternative imaging modality in patients undergoing TAVR.